Investigating the effect of hospital management accounting role on Covid19 crisis control - Salehi Kahyesh, Roya; Kamaei, Soleiman; Farhadi, Farbod (International Journal of Education and Cognitive Sciences, 2022)
Applying management accounting knowledge in government-affiliated institutions such as hospitals is essential. Due to the pandemic of Covid-19 disease around the world, various dimensions of societies, from the health system to the economy, have been affected. In three ways, the disease can affect business, the workplace and industry, and consequently the economy of societies.The Covid19 crisis shut down many companies and caused a recession. Obviously, managers cannot be prepared for all kinds of crises. However, if in crisis management as an integral part of their strategic management responsibility, the likelihood that their organizations will be in crisis is greatly reduced. It is important, to crisis management and its relationship to technical and operational planning. In recent years, the costs of the health services have increased dramatically; Over the past 30 years, the costs of health care services in the member states of the Organization for Economic Co-operation and Development (OECD) have tripled, and health care costs have become increasingly important.The aim of this study is to investigate the impact of management accounting innovations during the global epidemic crisis. The required data were collected from the system of the Ministry of Health and Medical Education and the impact of various factors on organizing the crisis was analyzed.The study looks at ways to manage the crisis in Covid 19 in the country and says that it helps to control the widespread and universal disease of Covid 19; Cultivation, education and accurate information and most importantly cost management with the help of management accounting knowledge.